A selective thyroid hormone β receptor agonist enhances human and rodent oligodendrocyte differentiation. Issue 9 (24th May 2014) - Baxi, Emily G.; Schott, Jason T.; Fairchild, Amanda N.; Kirby, Leslie A.; Karani, Rabia; Uapinyoying, Prech; Pardo‐Villamizar, Carlos; Rothstein, Jeffrey R.; Bergles, Dwight E.; Calabresi, Peter A.
<x xml:space="preserve">Abstract</x> Nerve conduction within the mammalian central nervous system is made efficient by oligodendrocyte‐derived myelin. Historically, thyroid hormones have a well described role in regulating oligodendrocyte differentiation and myelination during development; however, it remains unclear which thyroid hormone receptors are required to drive these effects. This is a question with clinical relevance since nonspecific thyroid receptor stimulation can produce deleterious side‐effects. Here we report that GC‐1, a thyromimetic with selective thyroid receptor β action and a potentially limited side‐effect profile, promotes in vitro oligodendrogenesis from both rodent and human oligodendrocyte progenitor cells. In addition, we used in vivo genetic fate tracing of oligodendrocyte progenitor cells via PDGFαR‐CreER;Rosa26‐eYFP double‐transgenic mice to examine the effect of GC‐1 on cellular fate and find that treatment with GC‐1 during developmental myelination promotes oligodendrogenesis within the corpus callosum, occipital cortex and optic nerve. GC‐1 was also observed to enhance the expression of the myelin proteins MBP, CNP and MAG within the same regions. These results indicate that a β receptor selective thyromimetic can enhance oligodendrocyte differentiation in vitro and during developmental myelination in vivo and warrants further study as a therapeutic agent for demyelinating models. GLIA 2014;62:1513–1529